Revisión Bibliográfica: La Inmunoglobulina y (Igy), Propiedades Y Usos En La Medicina Veterinaria (Monografía) (2021)
The research that is developed around immunoglobulins is a subject of great relevance in areas of human medicine, veterinary and related branches, since it allows have an approach that enables the comparison, contrast and analogy between such sciences; Under this idea it is possible to imagine a path of the biological sciences and in which common characteristics, functions and benefits can be identified of immunoglobulin Y of birds, and immunoglobulin G of mammals, since that some authors consider them analogous (Romero, Magnoli, & Peralta, 2014, p. 2). This path acquires greater relevance when general aspects such as are the fact that not all living beings have the same opportunity to carry I get an immune system strong enough to counteract the actions of some pathogenic agents and, therefore, need to be linked to procedures such as intravenous immunoglobulin therapy (IGIV) (Martínez, 2003, p. 259), which is nothing more than clinical assistance to those who present a diagnostic picture such as initially described, in order to adjust a type of balance around the system immunological.